PENGARUH PINJAMAN TUNAI DALAM KAPASITAS PENAWARAN PRODUK JASA TERHADAP FLUKTUASI PERMINTAAN KREDIT PELAKU USAHA KECIL PT. PERMATA FINANCE CIKUPA - Nurhadi, Nurhadi (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2015)
Credit is not foreign to the rapid economic growth higher in terms of supply and demand higher economic wheel rotates, the higher the economic fluctuations in macro it is a momentum shift melinium 2000 mega trends. banking act  no. 10 of 1998 explains the "provision of funds or equivalent claims based on a lending agreement or contract between the bank and other parties who require the borrower to pay off the debt after a certain period with interest". this is one form of government to provide banking regulation in order to stimulate the economy in the services non-banking one permata finance  tangerang. pt.permata finance at road  attacking front image cikupa market highway tangerang district, banten population in this study is 15 questions and a sample of 30 respondents. regression equation y = 9.584 + 186 + 402 + e results of hypothesis testing f count = 2,845, compared with f tables at the level of 5% error is obtain value of f table = 2.042, so f count> f table (2,845> 2,042), then ho rejected and ha accepted, meaning that there is influence between effect of cash loans in the capacity of the product offering services to fluctuation  in demand for loan  small businesses pt. permata finance cikupa researchers assume that the cash loans with collateral BPKB if without the assistance of the loan funds to invest so affect people's behavior become consumptive and be productive without the protection of the financial services authority should be the regulation of bank indonesia partici  fair to stabilize financial reputation in terms dimand and supply seen of monetary economics Keyword: credit, bpkb, micro economics, demand and supply